Kepastian Hukum Atas Kekuatan Pembuktian Akta Notaris yang Disangkal dalam Proses Peradilan - Elena Kristianto; Erny Kencanawati; Khoirul Anwar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Notarial deeds as authentic instruments hold a crucial role in Indonesia’s civil law evidence system, providing perfect proof under Article 1868 of the Civil Code. However, in practice, such deeds are often denied by one party in court, raising debates about the certainty of their evidentiary power. This study examines the legal consequences of denying a notarial deed for the parties in litigation and the assurance of legal certainty for those holding such deeds. Using R. Soeroso’s Theory of Legal Consequences and Jan Michael Otto’s Theory of Legal Certainty, this normative juridical research employs statutory, conceptual, analytical, and case approaches, with literature-based data collection and interpretative legal analysis. The findings reveal that denial of a notarial deed may create new legal relationships, alter good-faith relations into disputes, and result in sanctions imposed by court rulings. Meanwhile, legal certainty remains guaranteed, as authentic deed regulations are clear, binding, and enforceable, serving as a guideline in resolving disputes and upholding sanctions.